SHAPING LEADERSHIP: THE EFFECTS OF ONLINE TEACHING ON ACADEMIC LEADERS IN INDIAN HIGHER EDUCATION INSTITUTIONS - Singh, Jyoti; Srivastava, Rajlaxmi (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The study investigates teachers’ perceptions of online classes since the onset of the COVID-19 lockdown on March 25, 2020. It explores the transition from traditional education to EdTech and online assessment within the Indian educational system. The objective is to evaluate which of the demographic characteristics of academic leaders impact their adaptation to online teaching and to identify the challenges encountered during this transition. A quantitative approach was utilized, involving a demographic survey of 327 educators across India from public and private colleges. Data were collected through a 5-point Likert scale questionnaire, with reliability assessed using Cronbach’s alpha. Statistical analyses, including t-tests and ANOVA with Duncan’s Multiple Range Test, were conducted using IBM SPSS 25 to ensure precision. The results revealed that among the six demographic factors examined—age, gender, marital status, educational qualification, income level, and organization—only age, income, and educational qualification significantly affect the adoption of online teaching by faculty members in higher education institutions. Conversely, organization, marital status, and gender do not significantly influence the adoption of online teaching. These findings are pertinent for regulatory authorities and academic leaders as they revise policy frameworks, develop strategic initiatives, and establish technical infrastructures to facilitate the adoption of EdTech. Additionally, the insights gained can guide improvements in training and resources, particularly for institutions aiming to integrate online teaching into regular practice